Arquitectura social y terapéutica, el desarrollo de un equipamiento de resocializacion y rehabilitación en jóvenes con condición de calle de la localidad de los mártires Bogotá (2022)
The project was born from the need to safeguard life and be able to provide safe spaces to young people in poverty. This facility seeks to create spaces for rehabilitation and resocialization for adolescents who decide to leave the streets and are looking for a new life opportunity, in addition to being a home while they go through this process. The strategic location of the project enhances its attractiveness, because being close to the areas of high traffic of people in street conditions will allow them to arrive more easily, an integral equipment is proposed, which can provide safe and effective conditions from a social and therapeutic architecture for the correct development of a rehabilitation process in young people who so wish.